Application of the Bethesda system of reporting for cervical cytology to evaluate human papilloma virus induced changes in oral leukoplakia, oral squamous cell carcinoma, and oropharyngeal squamous cell carcinoma: A cytomorphological and genetic study. Issue 9 (24th June 2021) - Sivakumar, N.; Narwal, Anjali; Kumar, Sanjay; Kamboj, Mala; Devi, Anju; Pandiar, Deepak; Bhardwaj, Rashmi
Abstract: Background: Human papilloma virus (HPV) has a well‐established carcinogenic role in certain head and neck cancers. These HPV associated cancers possess unique clinicopathological behavior and exhibits better prognosis than their negative counterparts. Detection through polymerase chain reaction (PCR) has been considered as the "gold standard" but imposes burden in low resource settings. Therefore, in the present study, we assessed the validity of cytomorphological features for the detection of HPV in oral leukoplakia (OL), oral squamous cell carcinoma (OSCC), and oropharyngeal squamous cell carcinoma (OPSCC). Methodology: This study included 63 subjects comprising of 25 OL, 26 OSCC, and 12 OPSCC cases. Exfoliated cells were collected and processed for PCR followed by Papanicolaou staining and subsequent grading. Additionally the non‐classical signs were evaluated and statistical analysis included Chi‐square and Spearman's test. Result: 23/63 (36.5%) cases showed PCR positivity for HPV16. Most of the cytomorphological features showed significant correlation for the presence of HPV. A greater sensitivity and specificity was observed in the Bethesda system for reporting cervical cytology (TBS) than the Papanicolaou grading system. Conclusion: We conclude that the non‐classic cytological features could be employed in the detection of HPV in low resource settings with improved sensitivity. Liquid based cytology graded using TBS could be suitable for oral cytology in the detection of early atypical changes.